Improving Elementary School Students’ English Vocabulary Through Local Cultural Content Materials - Manurung, Frans; Harjanto, Ignatius (Widya Mandala Catholic University Surabaya, 2015)
Abstract Elementary students of a certain public school in Indonesia had difficulties in learning English. One of the crucial problems was learning English vocabulary. In an attempt to help the students learn and improve English vocabulary, the researchers decided to use CAR to teach English vocabulary with local cultural content materials. The aim of this study was to investigate how the teaching of English vocabulary with local cultural content materials contributed to the improvement of the students’ English vocabulary mastery. The topics covered in the materials were selected based on schemata theory. Vocabulary learning process was done through several activities provided in the materials: classroom and outside vocabulary learning. The results showed that the teaching of local cultural content materials have contributed to the improvement of the Elementary students’ vocabulary mastery. The schematic knowledge found in the familiar topics has aroused the students’ interest and motivation in learning English vocabulary. Students who were more familiar with the topics could respond to the vocabulary learning better than those who were not familiar with. The vocabulary mastery was more successful only if the students participated in both classroom and outside vocabulary learning process. Keywords: Vocabulary Mastery, Vocabulary Improvement, Local Cultural Content Materials, Vocabulary Learning, Schemata